The determinants of wind energy growth in the United States: Drivers and barriers to state-level development. (December 2018) - Schumacher, Kim; Yang, Zhuoxiang
Abstract: The focus of this paper is to analyse the determinants of wind energy development in the United States and how procedural and regulatory frameworks influence the deployment of wind power facilities. The empirical analysis uses statistical regression models integrating geospatial, macroeconomic and socio-environmental control variables. Using wind penetration as well as wind capacity additions as dependent variable permits a more differentiated analysis of both absolute and relative growth factors. This enables a precise assessment of state-to-state variations in permitting, zoning and siting procedures that wind developers have to clear before being authorised to start construction. Quantifying the number of state-level financial support measures and various permitting and regulatory process stages allowed for a more comprehensive assessment of administrative barriers to wind energy development than prior research studies. The results indicate a partial reversal of previous findings that showed that a high quantity of state-level regulations negatively affects wind capacity additions. Exogenous factors such as the ratio of in-state federal lands, population density, and especially wind energy potential, as well as federal statutes and incentives remain the main drivers of wind capacity additions and overall wind energy penetration. Contrasting prior literature, the influence of localised financial incentives or regulatory approval procedures appears to be minor; therefore streamlining national policies and incentives at the federal level might prove more effective than promoting wind development at the state level. We point out that future research should also examine the role of quality of state-level regulations in addition to quantity. Highlights: Most up-to-date United States state-level study using recent data sets from 2010 to 2016. Number of financial incentives & regulatory measures are weak growth indicators. Overall wind potential is the strongest driver of wind development. Novel dependent variable for wind penetration enables relative growth analysis. Quantity of environmental regulations did not influence energy growth.